Proposal of Venous Drainage–Based Classification System for Carotid Cavernous Fistulae With Validity Assessment in a Multicenter Cohort. Issue 3 (September 2015) - Thomas, Ajith J.; Chua, Michelle; Fusco, Matthew; Ogilvy, Christopher S.; Tubbs, R. Shane; Harrigan, Mark R.; Griessenauer, Christoph J.
Abstract : BACKGROUND: Carotid cavernous fistulae (CCFs) are most commonly classified based on arterial supply. Symptomatology and treatment approach, however, are largely influenced by venous drainage. OBJECTIVE: To propose an updated classification system using venous drainage. METHODS: CCFs with posterior/inferior drainage only, posterior/inferior and anterior drainage, anterior drainage only, and retrograde drainage into cortical veins with/without other drainage channels were designated as types 1, 2, 3, and 4, respectively. CCFs involving a direct connection between the internal carotid artery and cavernous sinus were designated as type 5. This system was retrospectively applied to 29 CCF patients. RESULTS: Our proposed classification was significantly associated with symptomatology ( P < .001). Type 2 was significantly associated with coexisting ocular/orbital and cavernous symptoms only ( P < .001), type 3 with ocular/orbital symptoms only ( P < .01), and type 4 demonstrated cortical symptoms with/without ocular/orbital and cavernous symptoms ( P < .01), respectively. There was a significant association of our classification system with the endovascular treatment approach ( P < .001). Types 1 and 2 were significantly associated with endovascular treatment through the inferior petrosal sinus ( P < .01). Type 3 was significantly associated with endovascular treatment through the ophthalmic vein ( P < .01) and type 5 with transarterial approach ( P < .01), respectively. Types 2 (27.6%) and 3 (34.5%) were most prevalent in this series, whereas type 1 was rare (6.9%), suggesting that some degree of thrombosis is present, with implications for spontaneous resolution. Type 2 CCFs demonstrated a trend toward partial resolution after endovascular treatment ( P = .07). CONCLUSION: Our proposed classification system is easily applicable in clinical practice and demonstrates correlation with symptomatology, treatment approach, and outcome. ABBREVIATIONS: CCF, carotid cavernous fistula ICA, internal carotid artery